Does the Nominal Exchange Rate Regime Matter? - Ostry, Jonathan (IMF Working Papers; Working Paper ;, 1995)
The effect of the exchange rate regime on inflation and growth is examined. The 30-year data set includes over 100 countries and nine regime types. Pegged regimes are associated with lower inflation than intermediate or flexible regimes. This anti-inflationary benefit reflects lower money supply growth (a discipline effect) and higher money demand growth (a credibility effect). Output growth does not vary significantly across regimes: Countries with pegged regimes invest more and are more open to international trade than those with flexible rates, but they experience lower residual productivity growth. Output and employment are more variable under pegged rates than under flexible rates.